Pengaruh Terapi Bermain pada Kemampuan Motorik Kasar Balita Kecanduan Ponsel - Depi Nurhaini; Netty Herawati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
One of your key roles as a parent is to stimulate your child's development, keeping children entertained. However, some parents do not have enough time to play with their children and choose to have mobile phones or other playthings at home to reduce the risk of children playing outside the home and to keep parents safe. . This affects the growth and development of children in terms of physical and mental performance as their gross motor skills are not honed. and uses the benefits of community activities to provide subjects with psychological interventions to develop gross motor function and divert attention from mobile phone play to games and activities. Fun activities like playing with toys, running, walking, climbing stairs, drawing, writing, and painting. The methods used in this study use qualitative methods in the research approach where the techniques used are observations and in-depth interviews with subjects. Data analysis used a reliability test. This technique is used to obtain a clearer picture of the outcome and the overall picture of the application of total exercise therapy in mobile phone-dependent infants.